Pemanfaatan Petunjuk arah Bilingual dalam tata Kelola Pariwisata di Desa Penembang - Dwisnu, Erlian; Dion, Selin; Darmawi, Darmawi; Ningrum, Sania Devita; Giovani, Edo (Jurnal Kewirausahaan dan Bisnis, 2021)
This research aims to provide a more comprehensive insight into the utilization of bilingual directions in tourism governance in Penembang Village. This study aims to provide a more comprehensive insight into how tourism destinations in Penembang Village are managed, as well as what factors have a role in the management process. This can help in developing better strategies to maintain and improve the management of these tourist destinations, as well as make a positive contribution to the experience of tourists visiting the region. With this research, tourism destination management can provide insight into how the tourism destination of Penembang Village is sustainable and successful in the long term.